CLOSTRIDIA ASSOCIATED WITH FOAL DIARRHEA IN EGYPT - J.ELJAKEE,; R.M.KHALIFA,; S.A.MAROUF,; SHALABY, B., (International Journal of Pharma and Bio Sciences, 2014)
Diarrhea is a common and important cause of suffering and loss in foals. The present work was to study the frequency of Clostridium infection in foal diarrhea and characterize C. perfringens toxins by multiplex polymerase chain reaction (PCR) and ELISA. By collection of fecal samples from both diarrheic (n=50) and apparently healthy (n=200) foals; Clostridium species were isolated with incidences of 30 and 7%, respectively. C. perfringens and C. sordellii were isolated alone from diarrheic cases with incidences of 8 and 2%, respectively and C. perfringens was isolated in a mixed form with C. sporogenes, C. sordellii, C. butyricum, C. tertium and C. bifermentans with the incidences of 2, 8, 2, 4 and 4%, respectively. The results of multiplex PCR confirmed the results of mice neutralization and dermonecrotic tests for typing C. perfringens toxins. ELISA results indicated that production of α-toxin among C. perfringens isolated from diarrheic foals was higher than apparently healthy foals.